Long-term soil mulching combined with N fertilizer could maintain soil water balance in semi-arid regions of Northwest China - Shenqiang Lv; Jia Li; Zeyu Yang; Huitong Li; Linquan Wang; Shenzhong Tian; Ahmed I. Abdo (Agricultural Water Management)
Soil mulching combined with nitrogen (N) fertilization has been widely applied to enhance crop yields and crop water productivity in (semi-) arid regions. However, its long-term effects on soil water balance are unclear. Therefore, a 6-year field experiment with five tillage treatments (CT: conventional tillage without mulch, RT: ridge-furrow tillage without mulch, PM: flat cultivation with plastic film mulch, RTPM: ridge-furrow cultivation with plastic film mulch on the ridge, SM: flat cultivation with straw mulch) and two rates of N fertilization (i.e., 0 kg N ha−1 and 225 kg N ha−1) was conducted on the Loess Plateau. Results showed that during normal or dry growing seasons, transpiration increases of 78.0 mm (PM) and 91.2 mm (RTPM) substantially exceeded evaporation decreases of 39.7 mm and 57.6 mm. Consequently, the application of PM and RTPM during dry or normal growing seasons resulted in soil water deficits of −38.9 mm and −42.0 mm, respectively. Conversely, during humid growing seasons, the transpiration increase mediated by PM (38.9 mm) and RTPM (30.7 mm) were markedly outweighed by respective evaporation reduction of 67.3 mm and 73.4 mm. Therefore, PM and RTPM enhanced soil water storage in humid growing seasons. Averaged across the humid and dry growing seasons, the evaporation reduction under PM and RTPM (53.5 mm and 65.5 mm) effectively offset the corresponding transpiration enhancement mediated by these treatments (58.5 mm and 61.0 mm). Furthermore, the rainfall during the humid growing seasons and fallow seasons partially offset the depletion of original soil water during the dry or normal seasons. Consequently, the average soil water balance of soil mulching remained positive (15.3 mm,13.1 mm and 16.1 mm under PM, RTPM and SM respectively). Additionally, soil mulching markedly enhanced transpiration/evapotranspiration ratio and water productivity, with increment of 5.7 %-15.3 % and 17.5 %-62.8 % relative to CT, respectively. Collectively, the integration of soil mulching with N application substantially improved water productivity; crucially, sustained soil mulching practices demonstrated non-depletive effects on soil water reserves. These findings validated the strategic recommendation for large-scale adoption of this integrated approach across globally distributed arid/semi-arid zones and other water-scarce agroecosystems.